Open economy macroeconomics in East Asia - Baharumshah, Ahmad Zubaidi (Ashgate Publishing Limited, 2005)
The East Asia countries were among the fastest growing economies in the world and of increasing importance to the world economy. These countries have taken the lead in adopting outward-oriented development policies. This volume focuses on the major issues on open economy macroeconomics in the East Asia economies that will be instructive to both academics and policymakers. The emphasis is on the countries that were severely affected by the 1997/98 Asian financial crises. Several aspects of exchange rate, current account, budget deficits, monetary and financial issues are considered in this book. In addition, several chapters are devoted to discussion on the issues of economic integration in the region. The contagion and the currency crisis are also discussed thoroughly. Most of the chapters are empirical in nature and the empirical evidence provided is based on the recent development in time series econometrics methods